Stability of a program manifold of control systems with locally quadratic relations - Zhumatov, S. S. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We establish sufficient conditions for the absolute stability of a program manifold of control systems. In the case where the Jacobi matrix is degenerate, sufficient conditions for the absolute stability of a program manifold is obtained by reduction to the central canonical form.